The neurology of gluten sensitivity - Pengiran Tengah, Dayangku Siti Nur Ashikin (2013)
Classical coeliac disease (CD) is a well-defined syndrome of small bowel villous atrophy associated with abdominal pain, malabsorption, and weight loss as a result of gluten-sensitivity, reversed rapidly by gluten exclusion diet. Disease associations include dermatitis herpetiformis (DH), Addison’s disease, type 1 diabetes mellitus, autoimmune thyroid disease and a variety of neurological disorders. This thesis aims to investigate the hypothesis of the existence of a gluten sensitive neurological disease